Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm looking for several ways to prove that $$\int_{0}^{\infty }\sin(x)x^mdx=\cos(\frac{\pi m}{2})\Gamma (m+1)$$

for $-2< Re(m)< 0$

share|cite|improve this question
What is your question? – Nick Peterson Jul 6 '13 at 16:58
@nrpeterson Perhaps the OP is looking for "several ways" to prove that integral. OP, perhaps you may share your way so that we can share our way. – Lord Soth Jul 6 '13 at 17:11
There must be some conditions! As an instance, for ¤m=0¤ the resukt is wrong. – kjetil b halvorsen Jul 6 '13 at 17:23
Wolphram alpha gives the range $-2<\text{Re}(m)<0$. – kjetil b halvorsen Jul 6 '13 at 17:39
@nrpeterson I'm looking for several ways to prove that integral – mhd.math Jul 6 '13 at 18:00
up vote 3 down vote accepted

Here is a fake proof: Let $x = \sqrt{t}$. Then

$$ \int_{0}^{\infty} x^{m} \sin x \, dx = \frac{1}{2} \int_{0}^{\infty} t^{m/2} \frac{\sin \sqrt{t}}{\sqrt{t}} \, dt. $$


$$ \frac{\sin \sqrt{t}}{\sqrt{t}} = \sum_{n=0}^{\infty} \frac{\phi(n)}{n!} (-t)^{n} \quad \text{for} \quad \phi(n) = \frac{n!}{(2n+1)!} = \frac{\Gamma(n+1)}{\Gamma(2n+2)}, $$

Ramanujan's master theorem gives

\begin{align*} \int_{0}^{\infty} t^{m/2} \frac{\sin \sqrt{t}}{\sqrt{t}} \, dt &= \Gamma\left(\frac{m}{2}+1\right)\phi\left(-\frac{m}{2}-1\right) \\ &= \frac{\Gamma\left(\frac{m}{2}+1\right)\Gamma\left(-\frac{m}{2}\right)}{\Gamma\left(-m\right)} = \frac{\Gamma\left(\frac{m}{2}+1\right)\Gamma\left(-\frac{m}{2}\right)}{\Gamma(m+1)\Gamma\left(-m\right)}\Gamma(m+1)\\ &= \frac{\sin \pi m}{\sin \left( \frac{\pi m}{2} \right)} \Gamma(m+1) = 2\cos\left(\frac{\pi m}{2} \right) \Gamma(m+1). \end{align*}

Therefore we have

$$ \int_{0}^{\infty} x^{m} \sin x \, dx =\cos\left(\frac{\pi m}{2} \right) \Gamma(m+1). $$

And here is a rigorous proof: By integration by parts, for $0 < a < b < \infty$,

\begin{align*} \int_{a}^{b} x^{m} \sin x \, dx &= \left[ x^{m} (1 - \cos x) \right]_{a}^{b} - \int_{a}^{b} m x^{m-1} (1 - \cos x) \, dx. \end{align*}

Since $ \Re m \in (-2, 0)$, $x^{m} (1 - \cos x)$ tends to $0$ either as $x \to 0^{-}$ or $x \to \infty$. This proves

$$ \lim_{\substack{a &\to& 0 \\ b &\to& \infty}} \left[ x^{m} (1 - \cos x) \right]_{a}^{b} = 0. $$

Also, by noting that $0 \leq 1 - \cos x \leq 1 \wedge x^2 $, we have

$$ \left| m x^{m-1} (1 - \cos x) \right| \leq |m| x^{\Re m-1} (1 \wedge x^{2}). $$

Since the RHS is integrable, the same is true for the LHS $m x^{m-1} (1 - \cos x)$. Thus the integral

$$ \int_{0}^{\infty} x^{m} \sin x \, dx $$

exists as (at least) in improper sense, and we have

\begin{align*} \int_{0}^{\infty} x^{m} \sin x \, dx &= - \int_{0}^{\infty} m x^{m-1} (1 - \cos x) \, dx \\ &= - \frac{m}{\Gamma(1-m)} \int_{0}^{\infty} \frac{\Gamma(1-m)}{x^{1-m}} (1 - \cos x) \, dx \\ &= - \frac{m}{\Gamma(1-m)} \int_{0}^{\infty} \left( \int_{0}^{\infty} t^{-m}e^{-xt} \, dt \right) (1 - \cos x) \, dx. \end{align*}

But since

\begin{align*} \int_{0}^{\infty} \int_{0}^{\infty} \left| t^{-m}e^{-xt} (1 - \cos x) \right| \, dtdx &\leq \int_{0}^{\infty} \int_{0}^{\infty} t^{-\Re m}e^{-xt} (1 - \cos x) \, dtdx \\ &= \int_{0}^{\infty} \frac{\Gamma(1-\Re m)}{x^{1-\Re m}} (1 - \cos x) \, dtdx < \infty, \end{align*}

Fubini's theorem shows that

\begin{align*} \int_{0}^{\infty} x^{m} \sin x \, dx &= - \frac{m}{\Gamma(1-m)} \int_{0}^{\infty} \int_{0}^{\infty} t^{-m}e^{-xt} (1 - \cos x) \, dxdt \\ &= - \frac{m}{\Gamma(1-m)} \int_{0}^{\infty} \frac{t^{-m-1}}{t^2 + 1} \, dt. \end{align*}

Applying the beta function identity and the Euler reflection formula for the Gamma function, it follows that

\begin{align*} \int_{0}^{\infty} x^{m} \sin x \, dx &= \frac{\pi m}{2\Gamma(1-m)} \csc \left( \frac{\pi m}{2} \right) = \cos \left( \frac{\pi m}{2} \right) \Gamma(m+1) \end{align*}

as desired.

share|cite|improve this answer
Why didn't you use the fact that the integrand is always nonnegative to justify switching the order of integration? – Random Variable Jul 6 '13 at 18:13
@RandomVariable, because OP assumed $m \in \Bbb{C}$ with $\Re m \in (-2, 0)$ so that $x^{m}$ is no longer real-valued, much less non-negative. And as you pointed out, this proof can be simplified further if we assume $m$ to be real. – Sangchul Lee Jul 6 '13 at 18:18

use the identities $ \int_{0}^{\infty}dxx^{m} exp(-ax)= \frac{\Gamma (m+1)}{a^{m+1}}$ $\qquad $$ i= exp(\pi i) $ and $ Re(exp(\pi s))=cos(\pi s) $ and you get your result

share|cite|improve this answer
This needs a justification to plug in $i$. – i707107 Jul 6 '13 at 21:09

Step1 Find that $$I_1(m)=\int_0^{\infty} \sin(x)x^m dx=\cos\frac{\pi m}{2}\Gamma(m+1),$$ $$I_2(m)=\int_0^{\infty}\cos(x)x^mdx=-\sin\frac{\pi m}{2}\Gamma(m+1),$$ for $-1<m<0$.

This can be done by coutour integration using quarter-circle contour.

Step2 The first integral $I_1(m)$ defines an analytic function on $-2<\Re m<0$.

This can be done by @sos440 's method of showing integrability.

Step3: Completion The identity for $I_1(m)$ should hold for all $m$ with $-2<\Re m<0$ by analytic continuation.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.